The Invisible Civil Servant: How Female Senior Lecturers in Sweden Narrate Work - Wall, Erika (Nordic Journal of Working Life Studies, 2020)
This article examines the public administration role of university personnel who are state employees by analyzing female senior lecturers’ stories on working in Swedish universities, especially regarding how their role as a civil servant is narrated as part of their work. A performative narrative approach was used to analyze the in-depth interviews of four female senior lecturers at Swedish universities. Through the analysis, three shared storylines emerged: I don’t think of myself as a civil servant; You have to keep a certain level and It’s a solitary duty.The study revealed how the senior lecturer position was narrated by the interviewees in terms of duties to students and the public and the lack of efficient social support and knowledge.The findings are discussed as gendered expressions of working as a female senior lecturer in Sweden.